Effect of graphene nanoplatelets (GNPs) content on improvement of mechanical and tribological properties of AZ31 Mg matrix nanocomposite. (April 2019) - Arab, M.; Marashi, S.P.H.
Abstract: The effect of Graphene nanoplatelets (GNPs) content on mechanical and tribological properties of AZ31 Mg matrix composite was investigated. Hardness was increased up to 14% by applying FSP and 41% via adding GNPs due to grain refinement, dynamic recrystallization and pinning effect of GNPs. Mechanical properties were improved by increasing the GNPs content which act as obstacle against dislocation glide. Quasi cleavage fracture of base metal was changed to dimple rupture in nanocomposite. Coefficient of friction was decreased 25–45% compared to base metal, by adding GNPs. Intensity of adhesive, abrasive and delamination wear mechanisms was decreased by increasing the GNPs through forming a lubricant layer which not only restricts frictional heat but also improves the load carrying capacity of nanocomposite. Highlights: Effect of GNPs content on tribological properties was studied for the first time. The COF value was decreased 25–45% comparing to BM by adding GNPs. Wear rate was decreased from 24 μg/m for BM to 10.2 μg/m by adding GNPs. The average microhardness was increased up to 41% by adding GNPs. Adding GNPs to BM changed the quasi cleavage fracture to dimple rupture.